The Role of Islamic Religious Education Teachers in Increasing the Self-Confidence of Students with Special Needs at SMP Muhammadiyah 4 Kebomas Gresik - Amirudin, Noor; Moh Tanjung Fajriansyah (Jurnal Hadratul Madaniyah, 2025)
Students with special needs at the junior high school level face unique challenges in developing self-confidence, especially during adolescence which has higher developmental complexity compared to elementary level. Students with Slow Learner and Speech Delay conditions at SMP Muhammadiyah 4 Kebomas show indicators of lack of self-confidence that can be seen from difficulties in interpersonal relationships, low academic achievement, poor self-image, communication difficulties, and social and academic adjustment problems. This study aims to analyze the role of Islamic Religious Education teachers in improving the self-confidence of students with special needs at SMP Muhammadiyah 4 Kebomas, particularly students with Slow Learner and Speech Delay conditions. In daily life, children with these conditions often experience quite diverse difficulties. They usually need more time to understand lessons compared to their peers, often feel insecure when having to speak in front of the class, and frequently become quiet because they are afraid of speaking incorrectly or not being understood by others.